Analisis Kelayakan Usaha Las Teralis Jendela Pada Bengkel Las Kertha Asih Jaya Melalui Penilaian Aspek Finansial - Wati, Wayan Adya; Nugroho, Andung Jati (CV. Ulil Albab Corp, 2024)
Mr. Gede Window Grille Welding Workshop initially had a capacity of 100 window grilles, which he wanted to expand to 200. The aim of this research is to find out whether it is feasible or not to develop a trellis welding business and increase the investment value to 200 window grills if viewed from the financial aspect. So it is necessary to carry out a financial feasibility analysis using net present (NPV), benefit cost ratio (BCR), internal rate of return (IRR), and payback period (PP) calculations. So it can be concluded that the window grille welding business from 100 window grilles is worth developing into 200 window grilles. If you look at the calculation results for 100 window grilles, the payback period value is 7,78 periods, so the return on investment capital is very fast because the income is quite high and large. PP 7,78 < 12 periods. The NPV value obtained from the research is Rp. 436.345.610 with data processing of DCF 6% (obtained from the 2023 BRI KUR interest rate). From the results obtained, the NPV > 0 means that the NPV > 0 category of the business being run is worthy of increasing its investment value to 200 window grilles. The IRR value obtained from the calculation is 28,68%, greater than DF, which is 6%. The feasibility of this business is also supported by the calculation results of the BCR, namely 3,124686. Where the business assessment category is said to be feasible is if the B/C ratio is > 1.